Malcolm Toon papers - Toon, Malcolm, 1916-
Chiefly scrapbooks containing correspondence, printed matter, reports, ephemera, photographs, briefing books, and other papers regarding the work of the U.S.-Russia Joint Commission on POW/MIA Affairs tracking military personnel missing from World War II, the Cold War, the Korean War, the Vietnamese conflict, and the Soviet occupation of Afghanistan. Also documents social activities of the commissioners which included Dmitrii Antonovich Volkogonov and Douglas Brian (Pete) Peterson.
Diplomat.
Collection material in English and Russian.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Peterson, Douglas Brian; Volkogonov, Dmitriĭ Antonovich; U.S.-Russia Joint Commission on POW/MIAs.; Prisoners of war; Cold War -- Missing in action; Cold War -- Prisoners and prisons; Korean War, 1950-1953 -- Missing in action; Korean War, 1950-1953 -- Prisoners and prisons; Vietnam War, 1961-1975 -- Missing in action; Vietnam War, 1961-1975 -- Prisoners and prisons; World War, 1939-1945 -- Missing in action; World War, 1939-1945 -- Prisoners and prisons; Afghanistan -- History -- Soviet occupation, 1979-1989 -- Missing in action; Afghanistan -- History -- Soviet occupation, 1979-1989 -- Prisoners and prisons; Diplomats